Roles and Perceptions of Kaizen Champions: A Study of Kaizen Implementation in Malaysian Automotive Industry - Mohd Ghazali, Maarof; Sorooshian, Shahryar; Suhaila, Abdul Hamid (Kolej Universiti Islam Antarabangsa Selangor, 2017)
Automotive industry in Malaysia provides vital contributions to Malaysian economy. To remain competitive in a globalised business environment, business players will have to ensure continuous improvement are being implemented as part of their business strategy. One of the tools for continuous improvement which has been accepted globally is kaizen. This paper provides some evidence from a larger study on kaizen implementation among automotive companies in Malaysia. It specifically attempts to understand the perceptions of kaizen champions and their role in kaizen implementation. Fifteen participants of semi-structured interviews conducted among automotive manufacturers and their suppliers in the Klang Valley and Pekan, Pahang areas invovled in the study. The data which was recorded during the interview was then transcribed and coded according to the relevant themes. The findings suggest that the role of kaizen champion is important to ensure successful kaizen implementation in organizations. The main role of kaizen champion is to lead and assist other staff members of the organizations to implement kaizen. Teamwork, trainings for employees and support from top management are also important in helping kaizen champion fulfil their roles. Findings from this study enrich our understanding on the kaizen implementation in Malaysia and are beneficial to companies which are going to embark into kaizen or having difficulties to sustain their kaizen activities. In addition, it could also be useful to the respective government agencies in implementing the appropriate strategies that could help automotive companies to sustain their operations.